Measuring the quality of adaptive environments in instruction based on student perceptions - Zahid Zufar At Thaariq; Dedi Kuswandi; Made Duananda Kartika Degeng (Inovasi Kurikulum, 2024)
Adaptive learning has been identified as a means of creating a student-centered environment that is more fulfilling in multiple aspects. Such an environment prioritizes the facilitation of students' interests in learning. The present study employs quantitative research methods to measure the quality of the adaptive learning environment at Wahid Hasyim Junior High School, as perceived by 144 students, using factor analysis techniques. The findings reveal several factors that are integral to the adaptive learning environment. Firstly, student interaction is deemed crucial, emphasizing interactive and personalized elements. Secondly, teachers' course delivery of learning is determined by design, models, strategies, and resources, with media use having a lesser impact. Thirdly, contextualized content and engaging instructional techniques are key factors in discovering and organizing learning materials. Finally, collaboration support is recognized as an essential factor. These conclusions can inform educational improvement initiatives at Wahid Hasyim Junior High School. AbstrakPembelajaran adaptif telah diidentifikasi sebagai cara untuk menciptakan lingkungan yang berpusat pada peserta didik yang lebih memuaskan dalam berbagai aspek. Lingkungan seperti ini memprioritaskan fasilitas minat peserta didik dalam belajar. Penelitian ini menggunakan metode penelitian kuantitatif untuk mengukur kualitas lingkungan belajar adaptif di SMP Wahid Hasyim, seperti yang dipersepsikan oleh 144 peserta didik, dengan menggunakan teknik analisis faktor. Temuan penelitian ini mengungkapkan beberapa faktor yang menjadi bagian integral dari lingkungan belajar adaptif. Pertama, interaksi peserta didik dianggap penting, dengan penekanan yang signifikan pada elemen interaktif dan personal. Kedua, penyampaian pembelajaran oleh guru ditentukan oleh desain, model, strategi, dan sumber daya, dengan penggunaan media yang memiliki dampak yang lebih kecil. Ketiga, konten yang kontekstual dan teknik pembelajaran yang menarik diidentifikasi sebagai faktor kunci dalam penemuan dan pengorganisasian materi pembelajaran. Terakhir, dukungan kolaborasi diakui sebagai faktor penting. Kesimpulan-kesimpulan ini memiliki potensi untuk menginformasikan inisiatif peningkatan pendidikan di SMP Wahid Hasyim.Kata Kunci: Lingkungan adaptif; pembelajaran; pendidikan; persepsi peserta didik.